The digital plenitude the decline of elite culture and the rise of digital media - Bolter, J. David 1951-
"There are two developments in the second half of the twentieth century have helped to define our media culture in the twenty-first. One is the rise of digital media: websites, videogames, social media, and mobile applications, as well as all the remediations of film, television, radio, and print that now appear in digital form. The other development is the end of our collective belief in what we might call Culture with a capital C. Since the middle of the twentieth century, traditional hierarchies of the visual arts, literature, and music as forms of creativity have broken down. This has been accompanied by a decline in the status of the humanities--literary studies in particular, but also history and philosophy. Jay Bolter's THE PLENITUDE is the story of how the dissolution of previously sacrosanct media institutions succumbed to the pervasive power of new forms of media. It is not an argument favoring an elite form of culture over popular culture, but rather a examination of how these changes have affected the divided societies we live in today"--Provided by publisher.